127k views
2 votes
Please answer
3(x-1)=5x+3-2x

User Kurt Huwig
by
5.5k points

2 Answers

5 votes
3x-3= 3x+3
You can’t really simplify it down more
User Nextar
by
5.4k points
6 votes
Answer: there are no solutions



Step by step: Step 1: Simplify both sides of the equation.
3
(
x

1
)
=
5
x
+
3

2
x
(
3
)
(
x
)
+
(
3
)
(

1
)
=
5
x
+
3
+

2
x
(Distribute)
3
x
+

3
=
5
x
+
3
+

2
x
3
x

3
=
(
5
x
+

2
x
)
+
(
3
)
(Combine Like Terms)
3
x

3
=
3
x
+
3
3
x

3
=
3
x
+
3
Step 2: Subtract 3x from both sides.
3
x

3

3
x
=
3
x
+
3

3
x

3
=
3
Step 3: Add 3 to both sides.

3
+
3
=
3
+
3
0
=
6
User Bert Hekman
by
5.1k points